Food and Beverage Management: For the Hospitality, Tourism and Event Industries - John Cousins; David Foskett; David Graham; Amy Hollier (Great Britain Goodfellow Publishers Ltd, 2019)
This fifth edition of the best-selling textbook Food and Beverage Management for the hospitality, tourism & event industries has been updated and revised to take account of current trends within education and the hospitality, tourism and leisure industries. In particular the consideration of the foods service cycle and includes greater account being taken of the management of foodservice operations within a broader business framework. It recognises that operations are not an end in themselves and food and beverage management is as much about the management of the business as it is about specific aspects of the food and beverage product. With a clear, user friendly, structure based on the Food Service Cycle, this fifth edition of Food and Beverage Management has been designed to meet the needs of those undertaking a range of educational programmes, from diploma to undergraduate levels, as well as supporting in-company training programmes.
Keywords: (ETB-2002) Food and Beverage Management